Gambaran Pengetahuan Ibu tentang Pemanfaatan Pangan Lokal untuk Meningkatkan Produksi ASI di Puskesmas Putri Ayu - Perwitasari, Tuhu; Nurita, Suci Rahmani; Fahkrunnisa, Lulu; Nurbaiti, Nurbaiti; Tiwi, Laida Sanilpa (Universitas Baiturrahim, 2025)
The natural role of women includes pregnancy, childbirth, and breastfeeding. However, these joyous moments can sometimes become frightening or even traumatic, especially for first-time mothers. Many expectant mothers feel pressured and fear that they will not be able to provide breast milk (ASI) for their babies. This fear often leads to real difficulties in breastfeeding. Breast milk is the best food for babies up to the age of two years. UNICEF states that exclusive breastfeeding can prevent up to 1.3 million deaths in children under the age of five. In Indonesia, many mothers still do not provide exclusive breastfeeding to their babies, and only a small percentage of newborns are breastfed within the first hour of life. The main reason for not breastfeeding or never breastfeeding is the lack of milk production, leading to the introduction of formula milk for infants aged 0-5 months.This research is a descriptive study with a cross-sectional approach. The study was conducted at the Putri Ayu Public Health Center in Jambi City from October 2023 to July 2024. The population in this study consists of all pregnant women at the Putri Ayu Public Health Center, and the sample was selected using accidental sampling techniques. Data analysis was performed using univariate analysis.The research findings indicate that mothers' knowledge about the utilization of local food to increase breast milk production involved 18 respondents. The majority of respondents (60%) had a moderate level of knowledge. It is recommended that healthcare providers and families continue to support pregnant women in utilizing local food to enhance breast milk production. This effort aims to achieve the exclusive breastfeeding program, ultimately reducing maternal mortality rates (AKI), infant mortality rates (AKB), and stunting.